Sensitivity correction of images obtained with the prototype Clear-PEM in pre-clinical environment - Teixeira, Ana Cristina da Fonseca (2013)
Dissertation presented at Faculdade de Ciências e Tecnologia Universidade Nova de Lisboa to obtain a Master Degree in Biomedical Engineering